Bacillus licheniformis-based intensive fermentation of Tibetan tea improved its bioactive compounds and reinforced the intestinal barrier in mice - Zhu, Hui; Zhou, Xiaoli; Shen, Caihong; Ao, Zonghua; Cao, Xiaonian; Song, Chuan; Mehmood, Muhammad Aamer; Wu, Tao; Mei, Jie; He, Manli; Ma, Yi; Wang, Ning (Frontiers in Microbiology, 2024)
Tibetan tea changes during microorganism fermentation. Research on microorganisms in Tibetan tea has focused on their identification, while studies on the influence of specific microorganisms on the components and health functions of Tibetan tea are lacking. Bacillus licheniformis was inoculated into Tibetan tea for intensive fermentation, and the components of B. licheniformis-fermented tea (BLT) were detected by liquid chromatography with tandem mass spectrometry (UHPLC-TOF-MS), and then the effects of BLT on intestinal probiotic functions were investigated by experiments on mice. The results revealed the metabolites of BLT include polyphenols, alkaloids, terpenoids, amino acids, and lipids. Intensified fermentation also improved the antioxidant capacity in vivo and the protective effect on the intestinal barrier of Tibetan tea. In addition, the enhanced fermentation of Tibetan tea exerted intestinal probiotic effects by modulating the relative abundance of short-chain fatty acid-producing bacteria in the intestinal flora. Therefore, intensive fermentation with B. licheniformis can improve the health benefits of Tibetan tea.